2005
DOI: 10.1590/s0101-81752005000400014
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura da comunidade de pequenos mamíferos (Mammalia, Rodentia) da Estação Ecológica de Águas Emendadas, Planaltina, Distrito Federal, Brasil

Abstract: Foram investigadas, no presente estudo a composição de espécies e a abundância de uma comunidade de pequenos mamíferos presentes nos campos de murundus, um tipo fitofisionômico característico da região central dos Cerrados brasileiros. Duas grades de armadilhas do tipo Sherman foram montadas e oito espécies de roedores foram capturadas. Não foi registrada a presença de nenhum marsupial na região. As espécies mais abundantes foram Bolomys lasiurus (Lund, 1841), Thalpomys lasiotis Thomas, 1916 e Calomys tener (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
1
16
0
8
Order By: Relevance
“…In forest fragments in southwest Mato Grosso, this species was the second most captured, also occurring in forest fragments' edges, but never in pasture (Santos-Filho et al, 2008b); in the Amazon, however, some individuals were observed crossing short pasturelands (about 300 m) surrounded by forest (MNFS, unpublished data). Necromys lasiurus was captured only in Cerrado sensu stricto areas in Cerrado in Alter do Chão (Magnusson et al, 1995), however Ribeiro and Marinho-Filho (2005) captured that species in murundus fields (grassland) in the Brazilian Federal District. In studies conducted by Santos-Filho et al (2008b), analysing fragmentation effects in southwest Mato Grosso, N. lasiurus and Calomys sp were more abundant in pasture, but there were captures inside forest fragments, demonstrating to be generalists about habitat use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In forest fragments in southwest Mato Grosso, this species was the second most captured, also occurring in forest fragments' edges, but never in pasture (Santos-Filho et al, 2008b); in the Amazon, however, some individuals were observed crossing short pasturelands (about 300 m) surrounded by forest (MNFS, unpublished data). Necromys lasiurus was captured only in Cerrado sensu stricto areas in Cerrado in Alter do Chão (Magnusson et al, 1995), however Ribeiro and Marinho-Filho (2005) captured that species in murundus fields (grassland) in the Brazilian Federal District. In studies conducted by Santos-Filho et al (2008b), analysing fragmentation effects in southwest Mato Grosso, N. lasiurus and Calomys sp were more abundant in pasture, but there were captures inside forest fragments, demonstrating to be generalists about habitat use.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in areas of Cerrado have shown that some species of small mammals have a strong preference for specific habitat types (Alho et al, 1986;Mares et al, 1986;Fonseca and Redford, 1984;Ribeiro and Marinho-Filho, 2005). Most studies about small mammals in Cerrado areas were conducted in the Brazilian Federal District by Alho (1981Alho ( , 1993; Fonseca and Redford (1984); Alho et al (1986); Mares et al (1986); ; Mares and Ernest (1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies dealing with only one type of habitat (e. g. Ribeiro and Marinho-Filho 2005;Becker et al 2007) or situated in transitional areas (i. e. Bezerra et al 2009) presented higher capture success rates (7-23 %). The pitfall trap success (around 1 %) was lower than that of live traps, similar to results found by Bezerra et al (2009) and Carmignotto and Aires (2011) but very distinct from the high pitfall success (7.5 %) presented by Cáceres et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recentes inventários em riachos da bacia do Alto Rio Paraná, principalmente na região Sudeste do Brasil, evidenciam a grande diversidade da bacia e revelam a especificidade desses ambientes frente à constante descoberta de novas espécies (Casatti et al 2001, Castro et al 2003, 2004, Langeani et al 2005, Apone et al 2008 Ribeiro et al (2008) identificaram 41 espécies de peixes para a unidade hidrográfica do Rio Paraná. Esses pesquisadores ressaltam, ainda, a importância biogeográfica desses mananciais hídricos e apontam o forte endemismo encontrado na região.…”
Section: Introductionunclassified